General methods for large-scale production of nanostructured V2O5 with controlled morphologies. (March 2019) - Wang, Shenghan; Yu, Ting; Li, Yeqiu; Fu, Haoyang; Sun, Chenglin
Graphical abstract: Highlights: The reported three routes for large scale production of V2 O5 nanomaterials were facile, cost-effective and green. Raman spectra, XRD spectra and SEM were employed to characterize the as-prepared V2 O5 materials. The formation mechanisms of each V2 O5 material were also discussed in depth. Abstract: V2 O5 especially in nano-size is widely applied in metallurgy, chemical industry, catalysis and energy storage. Great advances have been made in the area of fabricating nano-sized V2 O5 materials in bench scale recently. However, large-scale production of nano-sized V2 O5 materials remains a scientific and engineering challenge which hamper the corresponding commercialization process. Herein we report three facile methods for synthesizing V2 O5 nanomaterials with controllable morphologies such as nanobelts, nanorods and nanosheets through solution, thermal decomposition and hydrothermal processes, respectively. By optimizing previous methods, the V2 O5 products with controlled morphology were obtained in high yield. The morphologies and crystalline phases were characterized by scanning electrical microscopy, X-ray diffraction and Raman spectroscopy. Owing to the advantages of low-cost and high reproducibility, these methods can be potentially applied in large-scale production of nanostructured V2 O5 material for practical application.